2004
DOI: 10.1073/pnas.0401167101
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of transmembraneS-nitrosothiol transport

Abstract: S-nitrosothiols have been suggested to play an important role in nitric oxide (NO)-mediated biological events. However, the mechanisms by which an S-nitrosothiol (or the S-nitroso functional group) is transferred across cell membrane are still poorly understood. We have demonstrated previously that the degradation of S-nitrosoglutathione (GSNO) by cells absolutely required the presence of cystine in the extracellular medium and proposed a mechanism that involved the reduction of cystine to cysteine, followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
192
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(208 citation statements)
references
References 40 publications
15
192
1
Order By: Relevance
“…These two conditions were used to explore the S-nitrosoproteome of HASMC. The difference in the yield of protein S-nitrosocysteine between CysNO and the nitric oxide donor treatment may reflect the higher efficiency of S-nitrosylation by CysNO consistent with previous results (23). Cell culture studies have shown that exogenous CysNO is effectively transported intracellularly via the amino acid transporter system transporter system (23).…”
Section: Formation Of S-nitrosocysteine Protein Adducts In Human Aorticsupporting
confidence: 75%
See 1 more Smart Citation
“…These two conditions were used to explore the S-nitrosoproteome of HASMC. The difference in the yield of protein S-nitrosocysteine between CysNO and the nitric oxide donor treatment may reflect the higher efficiency of S-nitrosylation by CysNO consistent with previous results (23). Cell culture studies have shown that exogenous CysNO is effectively transported intracellularly via the amino acid transporter system transporter system (23).…”
Section: Formation Of S-nitrosocysteine Protein Adducts In Human Aorticsupporting
confidence: 75%
“…The difference in the yield of protein S-nitrosocysteine between CysNO and the nitric oxide donor treatment may reflect the higher efficiency of S-nitrosylation by CysNO consistent with previous results (23). Cell culture studies have shown that exogenous CysNO is effectively transported intracellularly via the amino acid transporter system transporter system (23). Consequently, intracellular CysNO may facilitate the formation of protein Snitrosocysteine adducts primarily by replenishment of endogenous S-nitrosoglutathione or by direct transnitrosation.…”
Section: Formation Of S-nitrosocysteine Protein Adducts In Human Aorticsupporting
confidence: 72%
“…Both NOͲdonors are cell permeable: SNOC can be transported into RBCs by the amino acid transporters LATͲ1 and 2 [42,43]. However, as a nitrosothiol, SNOC not only releases NO but is also an efficient nitrosating agent.…”
Section: Nitrosative Chemistry Of Dafͳfm Within Rbcsmentioning
confidence: 99%
“…It can be regulated via intracellular traffic and active plasma membrane transport of S-nitroso-L-cysteine by an L-type amino acid transport system (LATs of the SLC7 family) [158][159][160][161]. S-Nitrosothiols may be important component of the NO pathway, but this issue is problematic and controversially discussed with regard both to concentration and biological roles.…”
Section: S-nitrosothiols (Rsno)-in Biological Systems Pools Of Thiolmentioning
confidence: 99%